Pengaruh Jumlah Pelanggan Terhadap Tingkat Profitabilitas Pada Perusahaan Daerah Air Minum Di Kota Bengkalis - Mashuri Mashuri; Ninik Mardianis (JAS (Jurnal Akuntansi Syariah), 2020)
The purpose of this research was to determine the effect of the number of customers on the level of profitability in the Regional Water Company in Bengkalis City. This research is quantitative research. Data collection techniques using interview data and documentation. Data analysis techniques used are simple linear regression analysis, normality test, t-test and coefficient of determination test. This research shows that the results of the t-test obtained tcount (α) > ttable = 14.065 > 3.182 and the results of the test of the coefficient of determination are 0.985. So the results of this research are that there is a significant influence of the number of customers on the level of profitability in the Regional Water Company in Bengkalis City with a large influence of the remaining 98.5% of 1.5% influenced by other factors.